Human chorionic gonadotropin affects original (ovulatory) and induced (accessory) corpora lutea, progesterone concentrations, and pregnancy rates in anestrous dairy goats - Rodrigues, Juliana Nascimento Duarte (2022)
Two experiments were conducted in acyclic Alpine (A) and Saanen (S) goats that received intravaginal sponges containing 60 mg of medroxyprogesterone acetate for 6 days, as well as 200 IU of eCG and 30 μg d-cloprostenol i.m. 24 h before sponge removal. On day 7 (day 0 = onset of synchronized estrus), all goats were randomly divided into two groups: animals treated with 300 IU of hCG i.m. (hCG; Exp.1: n = 8A; Exp.2: n = 75A + S) and untreated controls (Control; Exp.1: n = 8A; Exp. 2: n = 70A + S). In Exp.2, all goats were artificially inseminated. Transrectal ovarian ultrasonography and blood collection were done on days 7, 10, 13, 17, and 21 (Exp.1), and pregnancy detection on day 60 (Exp.2). Estrus and ovulations occurred in five hCG and seven Control animals. Accessory CL (aCL) were detected in all hCG does. The total luteal area of ovulatory corpora lutea (oCL) increased (P < 0.05) on day 10 in hCG does and remained greater (P < 0.05) than in Control until day 21. Total and high-velocity color Doppler area were greater (P < 0.05) for oCL of hCG does on days 13 and 17. Progesterone concentrations were greater (P < 0.05) in hCG does from days 13 to 21 and related directly to the total luteal and oCL area for the duration of the study in all does. The pregnancy rate was higher (P < 0.05) in hCG than in Control by 22.5 %. Human chorionic gonadotropin given on day 7 of the synchronized estrous cycle positively affected CL function and pregnancy rates in seasonally anovular dairy goats.